Analisis Pengaruh Pengawasan Keselamatan dan Penggunaan APD Terhadap Statistik Kecelakaan Kerja di PT XYZ - Haykal A. Fadhli; Rizqi N. Sari (Jurnal Serambi Engineering, 2025)
Workplace accidents are a serious problem that can result in physical injury, economic loss and a negative impact on business productivity. Inadequate use of personal protective equipment (PPE) or lack of safety supervision often contribute to the occurrence of workplace accidents. Although many organisations have implemented various safety policies, challenges remain in reducing the number of accidents. This study aims to analyse the impact of safety supervision and the use of PPE on workplace accident statistics at PT XYZ. The methodology used is a descriptive quantitative approach with correlation analysis, using primary data from interviews with HSE staff and secondary data from annual HSE reports during the period 2020-2023. The results show a decrease in the number of workplace accidents from 41 cases in 2020 to 20 cases in 2023, as well as a decrease in the frequency rate (FR) from 10.92 to 5.85 per million working hours. However, the negative Safe T score indicates that accident prevention programmes have not significantly changed the overall results. Recommendations from this study include increasing the intensity of safety inspections, developing ongoing training programmes for employees, and promoting interdepartmental collaboration to create a safer work environment.